Musical learning in maturity: dialogue between theory and practice (Per Musi, 2015)
This work presents a partial synthesis of the master’s research concluded in 2010, and aims at discussing the meaning of musical learning and its relation to theory and practice, taking into account the intention and musical ability of mature adults. Under this qualitative approach with techniques of educational ethnography, the paper brings the reports of eight students over 50 years old who participated of semi-structured interviews during the community course Appraising and Musicalization in Maturity – UFMG. The results derive from the interpretative analysis of content, based on the ideas of SWANWICK (2003; 1996) and GREEN (2005). The final considerations consider the importance of adapting methods of musical learning for this age range, combining basic theory and practical activities in accordance to the possibilities and experience of the learner.